Inflammation and Cancer: Extra- and Intracellular Determinants of Tumor-Associated Macrophages as Tumor Promoters. (18th January 2017) - Szebeni, Gabor J.; Vizler, Csaba; Kitajka, Klara; Puskas, Laszlo G.
Abstract : One of the hallmarks of cancer-related inflammation is the recruitment of monocyte-macrophage lineage cells to the tumor microenvironment. These tumor infiltrating myeloid cells are educated by the tumor milieu, rich in cancer cells and stroma components, to exert functions such as promotion of tumor growth, immunosuppression, angiogenesis, and cancer cell dissemination. Our review highlights the ontogenetic diversity of tumor-associated macrophages (TAMs) and describes their main phenotypic markers. We cover fundamental molecular players in the tumor microenvironment including extra- (CCL2, CSF-1, CXCL12, IL-4, IL-13, semaphorins, WNT5A, and WNT7B) and intracellular signals. We discuss how these factors converge on intracellular determinants (STAT3, STAT6, STAT1, NF- κ B, RORC1, and HIF-1 α ) of cell functions and drive the recruitment and polarization of TAMs. Since microRNAs (miRNAs) modulate macrophage polarization key miRNAs (miR-146a, miR-155, miR-125a, miR-511, and miR-223) are also discussed in the context of the inflammatory myeloid tumor compartment. Accumulating evidence suggests that high TAM infiltration correlates with disease progression and overall poor survival of cancer patients. Identification of molecular targets to develop new therapeutic interventions targeting these harmful tumor infiltrating myeloid cells is emerging nowadays.